Community participation in governance for sustainable management of medicinal plants market in urban area - Foo, Jurry; Abdul Latiff Mohamad; Mustafa Omar; Ahmad Aldrie Amir (Universiti Kebangsaan Malaysia, 2016)
Community participation (CP) in governance is important for better management of medicinal plant’s market in the urban area. The basic concept of sustainability is described as meeting the needs of present generation without compromising the needs of future generations, with concern to economics, social and natural environment. Communities have the right to voice out their needs toward medicinal plants. This paper describes community participation in governance through their attitude and how governance response. Generally, there is a two-way interaction between authority and community to ensure the medicinal plant’s market fulfil both parties’ needs. As for the communities, they voice out their needs through attitude by giving response, reaction and action. While the authority take in account to the attitude to design a suitable policy in planning, implementation, enforcement and reviews for better management that achieve both needs by the time and for the future.